Review of Islamic Law on Pemmali Kawing Kembar in Cening Village, West Malangke, North Luwu - Hasnia, Hasnia; Assaad, Andi Sukmawati; Arif, Firman Muhammad (Journal of Family Law and Islamic Court, 2025)
This thesis discusses the Pemmali of Twin Marriages in Sibling Relationships Case Study of Cenning Village, West Malangke District, North Luwu Regency. This study aims to determine and understand the implementation and review of Islamic law in the twin marriage contract of sibling relationships. This type of research is qualitative research with an an empirical and historical juridical approac approach. The data sources used in this research are primary and secondary data. Then the data collection techniques in this research are observation, interviews, and documentation, data management techniques, namely using inductive methods, deductive methods, comparative methods and drawing conclusions. The results of the study found that the implementation of a twin marriage contract in a sibling relationship is the same as a marriage contract general; the only difference is that one of the brides does the marriage contract one day before the reception, and the other bride does the contract on the day of the reception because the people of Cenning village believe that if the marriage contract is carried out simultaneously, it will result in problems from for one of the twin marriage brides. Meanwhile, in the review of Islamic law, pemmali twin marriages in sibling relationships are permissible, because based on the results of research in their implementation.